2015
DOI: 10.1155/2015/751425
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of Fracture Resistance of Simulated Immature Teeth Restored with Glass Fiber Posts, Intracanal Composite Resin, and Experimental Dentine Posts

Abstract: Aim. The aim of this study was to compare the fracture resistance of simulated immature teeth restored with gutta-percha, glass fiber posts (GFP), experimental dentine posts (DP) or Intracanal composite Resin (ICR). Materials and Methods. Fifty maxillary canines were decoronated, standardized and enlarged until, number 5 Peeso reamers were allowed to simulate immature teeth. After placement of 5 mm of MTA, the canals were divided into 5 groups and filled as follows: Group 1: AH Plus + gutta-percha, lateral com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Possible strengthening of traumatized anterior teeth with wide root canals, by inserting adhesively luted fibre posts, has been suggested (Ree & Schwartz 2017). However, the results of in vitro studies are controversial (Carvalho et al 2005, Seto et al 2013, Brito‐Júnior et al, 2014, Nikhil et al 2015, Topcuoglu et al 2015) and more clinical data are required to support the assumption of strengthening.…”
Section: Reviewmentioning
confidence: 99%
“…Possible strengthening of traumatized anterior teeth with wide root canals, by inserting adhesively luted fibre posts, has been suggested (Ree & Schwartz 2017). However, the results of in vitro studies are controversial (Carvalho et al 2005, Seto et al 2013, Brito‐Júnior et al, 2014, Nikhil et al 2015, Topcuoglu et al 2015) and more clinical data are required to support the assumption of strengthening.…”
Section: Reviewmentioning
confidence: 99%
“…2014, Nikhil et al . 2015), whilst others could not demonstrate an additional effect (Carvalho et al . 2005, Seto et al .…”
Section: Endodontic Treatment Of Immature Teeth With Nonvital Pulpsmentioning
confidence: 96%
“…However, there is limited evidence on the additional benefit of a bonded root canal post in immature teeth with only minor loss of coronal tooth structure. Some laboratory studies reported that the use of fibre posts improved the fracture resistance of immature teeth significantly more than composite resin alone (Schmoldt et al 2011, Brito-Junior et al 2014, Nikhil et al 2015, whilst others could not demonstrate an additional effect (Carvalho et al 2005, Seto et al 2013. Backfilling the remaining part of the root canal with guttapercha and sealer resulted in the weakest roots (Schmoldt et al 2011, Brito-Junior et al 2014, Nikhil et al 2015.…”
Section: Endodontic Treatment Of Immature Teeth With Nonvital Pulpsmentioning
confidence: 99%
See 2 more Smart Citations